2007
DOI: 10.1149/1.2404779
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Poisoning and Regeneration of Ni-Based Anodes in Solid Oxide Fuel Cells

Abstract: The effect of hydrogen sulfide ͑H 2 S͒ on the performance of nickel/yttria-stabilized zirconia ͑YSZ͒ cermet anode for solid oxide fuel cells has been studied under various operating conditions. In all cases, a small amount of H 2 S ͑ppm level͒ causes a sharp drop in cell performance within the first few minutes of exposure, followed by a gradual but persistent deterioration in performance for several days. The extent of anode degradation caused by sulfur poisoning increases with increasing H 2 S concentration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

27
272
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(305 citation statements)
references
References 29 publications
27
272
3
3
Order By: Relevance
“…In good agreement with thermodynamics [9,20] and calculations based on density functional theory (DFT), [27] it has been demonstrated in several electrochemical studies that the extent of sulphur poisoning is a function of temperature, oxygen partial pressure and sulphur concentration as well as chemical nature of fuel and anode material [28e30]. Several studies have demonstrated that there is an initial reversible (or partially reversible) degradation step during the very first minutes when the anode is exposed to H 2 S [9,12,31], followed by a slow, but continuous, non-reversible decrease of electrode performance [9,12,31]. First, rapid decrease of electrochemical performance is likely caused by adsorption of sulphur species at electrode and concomitant blocking of the socalled three-phase-boundary (TPB) for hydrogen oxidation [9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In good agreement with thermodynamics [9,20] and calculations based on density functional theory (DFT), [27] it has been demonstrated in several electrochemical studies that the extent of sulphur poisoning is a function of temperature, oxygen partial pressure and sulphur concentration as well as chemical nature of fuel and anode material [28e30]. Several studies have demonstrated that there is an initial reversible (or partially reversible) degradation step during the very first minutes when the anode is exposed to H 2 S [9,12,31], followed by a slow, but continuous, non-reversible decrease of electrode performance [9,12,31]. First, rapid decrease of electrochemical performance is likely caused by adsorption of sulphur species at electrode and concomitant blocking of the socalled three-phase-boundary (TPB) for hydrogen oxidation [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that there is an initial reversible (or partially reversible) degradation step during the very first minutes when the anode is exposed to H 2 S [9,12,31], followed by a slow, but continuous, non-reversible decrease of electrode performance [9,12,31]. First, rapid decrease of electrochemical performance is likely caused by adsorption of sulphur species at electrode and concomitant blocking of the socalled three-phase-boundary (TPB) for hydrogen oxidation [9,12]. There is some consensus about the first step of poisoning, but there are several significantly different if not controversial views about the second, slower step.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is important to understand and quantify the sulfur tolerance of SOFC anodes in the event of sulfur breakthrough from the desulfurizer. Sulfur poisoning of Ni-YSZ anodes in SOFC is well studied experimentally for model fuel compositions consisting of ppm levels of H 2 S in mixtures of H 2 , H 2 O and an inert [2][3][4] as well as H 2 S in gas mixtures representative of natural gas or reformed natural gas. [5][6][7][8] Most of the experimental literature deals with H 2 S concentrations well below 10 ppm and work that treats H 2 S concentrations higher than 20 ppm is rather limited.…”
mentioning
confidence: 99%
“…[5][6][7][8] Most of the experimental literature deals with H 2 S concentrations well below 10 ppm and work that treats H 2 S concentrations higher than 20 ppm is rather limited. 2,5,8 On the other hand it is well known that natural gas and biogas can have substantially higher sulfur concentrations and that catalytic steam reforming of methane can be carried out on Ni even with 100 ppm H 2 S without losing all catalytic activity 9,10 e.g., a methane conversion (in model biogas) of ∼35% can be maintained using a supported Ni catalyst with 100 ppm H 2 S at 800…”
mentioning
confidence: 99%
See 1 more Smart Citation